Which Individual or Organization is Responsible For Career Planning? (Literature Review) - Setiawan, Totok Andi; Indriati, Fibria (Dinasti Research, 2024)
Career is important in the life of employees, and humans have the desire to continue to develop and advance. Therefore, there is a need for clear career planning in order to align the interests of individuals and organisations. Career planning is divided into two, namely individual career planning and organisational career planning. It is still debatable who is responsible for career planning, individuals or organisations. This research is a qualitative research with a literature study approach. The literature used in this research are national and international scientific books and articles. The purpose of this research is to find out who is responsible for career planning. It was found that good career planning will identify strengths and weaknesses as well as abilities that must be fulfilled to face the future. With career planning will provide a career path that can be travelled by employees. Career planning should be made realistically not just a career goal. The result of the research is that individuals have responsibility in their careers, because individuals know exactly what their interests and talents are. However, the organisation must facilitate individuals to develop in their careers.